Carcass, meat quality traits, and economic analysis of Nellore bulls fed with finishing feedlot diets containing mechanically processed corn silage - Costa, C. [UNESP]; Baldassini, W. A. [UNESP]; Leal, M. S. [UNESP]; Meirelles, P. R.L. [UNESP]; Castilhos, A. M. [UNESP]; Nascimento Júnior, N. G. [UNESP]; Silveira, J. P.F. [UNESP]; Pariz, C. M. [UNESP]; Roça, R. O. [UNESP]; Factori, M. A. [UNESP]; Silva, M. G.B. [UNESP] (Springer Nature, 2023)
Effects of mechanical processing (MP) of corn silage and its inclusion in feedlot diets on carcass and meat quality traits of Nellore (Bos indicus) were analyzed. Seventy-two bulls aged approximately 18 months and with an initial average body weight of 392.8 ± 22.3 kg were used. The experimental design was a 2 × 2 factorial arrangement, considering the concentrate–roughage (C:R) ratio (40:60 or 20:80), MP of silage and their interactions. After slaughter, hot carcass weight (HCW), pH, temperature, backfat thickness (BFT), and ribeye area (REA), yields of meat cuts (tenderloin, striploin, ribeye steak, neck steak, and sirloin cap), meat quality traits and economic analysis were evaluated. A lower final pH was found in the carcasses of animals consuming diets containing MP versus unprocessed silage (pH = 5.81 versus 5.93). Carcass variables (HCW, BFT, and REA) and meat cut yields were not affected by treatments. The C:R 20:80 increased the intramuscular fat (IMF) content by approximately 1%, without affecting moisture, ash, and protein contents. Meat/fat color (L*, a* and b*) and Warner–Bratzler shear force (WBSF) were similar among treatments. The results indicated that the MP of corn silage in finishing diets can provide better carcass pH results in Nellore bulls, without negatively influencing carcass weight, fatness, and meat tenderness (WBSF). The IMF content of meat was slightly improved using a C:R 20:80 and lower total costs per arroba produced (3.5%), daily costs per animal/day (4.2%), and cost per ton of feeds (5.15%) were found with MP silage.
Keywords: Beef cattle; Bos indicus; Corn plants; Feed processing; Zea mays